This paper is on the rational choice theory and the choice of healthcare services for the treatment of malaria in Nigeria. It focuses on the factors that influence or determine the choice malaria treatment using the rational choice theory as the basis. It was discovered that there were many determinants of what informs the maximum utility but it is all wrapped up in the organization of the health care system. Hence, in choosing treatment for malaria, factors like; perceived and actual quality of care, proximity of the services, accessibility, cost of treatment, socio-economic status of the patients, availability of services, etc., are important. These factors in many occasions constitute constraints which in turn makes choices explicit and then patients makes trade-offs between alternatives. (2013)
This paper is on the rational choice theory and the choice of healthcare services for the treatment of malaria in Nigeria. It focuses on the factors that influence or determine the choice malaria treatment using the rational choice theory as the basis. It was discovered that there were many determinants of what informs the maximum utility but it is all wrapped up in the organization of the health care system. Hence, in choosing treatment for malaria, factors like; perceived and actual quality of care, proximity of the services, accessibility, cost of treatment, socio-economic status of the patients, availability of services, etc., are important. These factors in many occasions constitute constraints which in turn makes choices explicit and then patients makes trade-offs between alternatives.